Determinasi Keberhasilan Kinerja Berbasis Strategi Unggul BMT UAS Kantor Cabang Bangilan sebagai Kantor Terbaik Tahun 2024 - Ilmiyah, Izzatul (Journal of Islamic Finance and Syariah Banking, 2025)
The growth of Islamic microfinance institutions in Indonesia has significantly contributed to expanding access to Islamic-based finance. However, amidst digital transformation and competition from modern financial institutions, many Baitul Maal wat Tamwil (BMT) face serious challenges in maintaining their performance and sustainability. The urgency of this research lies in the importance of understanding the determinants of BMT performance success through the implementation of superior strategies that adapt to the social and economic dynamics of the community. This study aims to analyze the determinants of successful performance based on superior strategies at BMT UAS Bangilan Branch, which was awarded the title of best office in 2024. This research used a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results indicate that the success of BMT UAS Bangilan Branch is determined by the synergy between human resource development, digital technology utilization, Sharia product innovation, promotional strategies, and member services that are responsive to community needs. Supporting factors such as community trust and central management support strengthen this strategy, while limited technological infrastructure and digital literacy pose major challenges. This research provides academic contributions to the literature on Islamic value-based strategic management as well as practical recommendations for strengthening BMT governance in Indonesia.